2002
DOI: 10.1029/2001jd001385
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of background aerosol and subvisible cirrus in the tropical tropopause region

Abstract: [1] In situ aerosol measurements were performed in the Indian Ocean Intertropical Convergence Zone (ITCZ) region during the Airborne Polar Experiment-Third European Stratospheric Experiment on Ozone (APE-THESEO) field campaign based in Mahe, Seychelles between 24 February and 6 March 1999. These are measurements of particle size distributions with a laser optical particle counter of the Forward Scattering Spectrometer Probe (FSSP)-300 type operated on the Russian M-55 high- altitude research aircraft Geophysic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 37 publications
(71 reference statements)
4
57
2
Order By: Relevance
“…A step forward in this discussion was made recently: Krämer et al (2009) observed ice crystal concentrations much lower than expected (most often < 0.1 cm −3 ), but consistent with the high supersaturations measured. These observations turned the "supersaturation" into a "nucleation puzzle", which is supported by earlier measurements of low ice crystal numbers (McFarquhar et al, 2000;Thomas et al, 2002;Lawson et al, 2008). The "nucleation puzzle" is currently being intensely discussed and other nucleation pathways suppressing, modifying or replacing homogeneous freezing have been proposed (Kärcher and Koop, 2005;Gensch et al, 2008;Murray, 2008;Zobrist et al, 2008;Krämer et al, 2009;Spichtinger and Gierens, 2009c;Murray et al, 2010;Jensen et al, 2013).…”
Section: P Spichtinger and M Krämer: Tropical Tropopause Ice Cloudsmentioning
confidence: 52%
“…A step forward in this discussion was made recently: Krämer et al (2009) observed ice crystal concentrations much lower than expected (most often < 0.1 cm −3 ), but consistent with the high supersaturations measured. These observations turned the "supersaturation" into a "nucleation puzzle", which is supported by earlier measurements of low ice crystal numbers (McFarquhar et al, 2000;Thomas et al, 2002;Lawson et al, 2008). The "nucleation puzzle" is currently being intensely discussed and other nucleation pathways suppressing, modifying or replacing homogeneous freezing have been proposed (Kärcher and Koop, 2005;Gensch et al, 2008;Murray, 2008;Zobrist et al, 2008;Krämer et al, 2009;Spichtinger and Gierens, 2009c;Murray et al, 2010;Jensen et al, 2013).…”
Section: P Spichtinger and M Krämer: Tropical Tropopause Ice Cloudsmentioning
confidence: 52%
“…The distribution extends down to the sizes of the freezing aerosol particles (0.5-1 µm), indicative of ongoing freezing. Interestingly, this feature is seen in young midlatitude (Schröder et al, 2000) and thin tropical cirrus (Thomas et al, 2002) ice crystal size distributions. However, difficulties in www.atmos-chem-phys.org/acp/0000/0001/ Atmos.…”
Section: Ice Crystal Size Distributions and Dehydrationmentioning
confidence: 96%
“…In principle the histogram may consist of up to 40 unequal size bins, but this resolution is usually reduced to below 10 bins (7 in the present study) to overcome ambiguities linked to the relationship between light scattering intensity and particle size, which is not always univocal, and to increase the counting statistics in the single bin. The uncertainties of the number concentrations reported by the FSSP are determined by the uncertainty of the sample volume (approximately 20%) and mostly by poor counting statistics at low number densities like those encountered in thin or subvisual cirrus clouds (Thomas et al, 2002). To increase counting statistics, data are averaged over 10 s in cirrus clouds, or to several minutes in clear air.…”
Section: Instruments and Measurementsmentioning
confidence: 99%
“…and modal radius of few tens of µm on a similar thin subvisible cirrus layer over the tropical central Pacific. Size distributions of cirrus clouds in the upper tropical troposphere, exhibiting size diameters with pronounced peak at 10 µm, have been reported by Thomas et al (2002), presenting observations taken on board the high altitude research aircraft M55 Geophysica. Ultrathin tropical tropospheric clouds (UTTC) were observed directly beneath the tropical tropopause, characterised by a very low ice crystal number concentration (0.05 cm −3 ), and a size diameters modal peak of 10 to 12 µm .…”
Section: Introductionmentioning
confidence: 99%